"Perform'd in this wide gap of time": A Stage History of The Winter's Tale. Issue 1 (May 2020) - Baker, Christopher
Abstract : The stage history of Shakespeare's The Winter's Tale reflects changing critical perceptions about its themes as well as an evolution of theatrical production over a span of four centuries. First noted in astrologer Simon Forman's record of a performance on May 15, 1611, the play was popular with court audiences but disappeared from the stage when the theatres were closed at mid-century. It reappeared in a truncated performance on January 15, 1741. Nine months later David Garrick offered his abbreviated text—essentially a maudlin, three-act pastoral diversion—to popular appeal but critical censure. In 1802, John Philip Kemble's production presented a fuller, though Bowdlerized, text, featuring the great Sarah Siddons as Hermione. Hermione's role increasingly reflected the Victorian image of the selfless spouse who maintains her moral fiber under duress. During Charles Kean's directorship at the Princess's Theatre starting in 1850, the play acquired more lavish sets and scenery intended to reflect the historical context of the action, but the text sank under the weight of such ponderous efforts at realism. With the arrival of Harley Granville Barker's 1912 production at the Savoy Theatre, the play was returned to a more Elizabethan identity; a smaller, less cluttered stage permitted a faster-paced production with greater attention paid to Leontes as a psychologically fragile husband and monarch. This emphasis on the play as a study of the troubled marriage of a troubled king has persisted into the twentieth century as directors such as Jane Howell and Gregory Doran have lent this romance a convincing emotional depth.